VDR activation of intracellular signaling pathways in skeletal muscle - Boland, Ricardo Leopoldo (2011)
The purpose of this article is to review the activation of signal transduction pathways in skeletal muscle cells by the hormone 1α,25(OH) 2-vitamin D 3 [1α,25(OH) 2D 3], focusing on the role of the vitamin D receptor (VDR). The hormone induces fast, non transcriptional responses, involving stimulation of the transmembrane second messenger systems adenylyl cyclase/cAMP/PKA, PLC/DAG+IP 3/PKC, Ca 2+ messenger system and MAPK cascades. Short treatment with 1α,25(OH) 2D 3 induces reverse translocation of the VDR from the nucleus to plasma membranes. Accordingly, a complex is formed in the caveolae between the VDR and TRCP3, integral protein of capacitative Ca 2+ entry (CCE), suggesting an association between both proteins and a functional role of the VDR in 1α,25(OH) 2D 3 activation of CCE. Stimulation of tyrosine phosphorylation cascades by 1α,25(OH) 2D 3 have demonstrated the formation of complexes between Src and the VDR. Through these mechanisms, 1α,25(OH) 2D 3 plays an important function in contractility and myogenesis. © 2011 Elsevier Ireland Ltd.